Menggali Makna Pengalaman Mahasiswa Mengembangkan Civic Engagement Melalui Kampus Mengajar - Raudoh Alawiyah, Risti; Martini, Eneng; Pandikar, Ernandia (STKIP Pasundan, 2025)
This research is motivated by one of the MBKM Programs, namely Teaching campus, which is a teaching assistance program targeting schools affected by the pandemic that are in the 3T area and have low literacy and numeracy skills. Citizen involvement is known as civic engagement. In tihis program, students carrying out their duties as citizens known as agents of change are required to become problem solvers. This is due to the results of the PISA survey to measure the literacy and numeracy skills of students in 79 countries showing that Indonesia is in the bottom 10th place. This research uses a qualitative approach with the phenomenological method. Data was collected through interviews, observations, and documentation studies 4 STKIP Pasundan students who had participated in the campus teaching program. The research result show that student involvement in this program has a good impact on the students assigned school for the students themselves, the implementation of the campus teaching program is going well. Students understanding of civic engagement through campus teaching program includes: developing social awareness and concern, developing a sense of responsibility, and strengthening identity and citizen abilities.